1993
DOI: 10.1111/j.1365-2222.1993.tb02480.x
|View full text |Cite
|
Sign up to set email alerts
|

Elimination diet and intestinal permeability in atopic eczema: a preliminary study

Abstract: We measured small intestinal permeability to lactulose and rhamnose in 18 healthy children and in 15 children with atopic eczema, before and after a 14-day elimination diet. The children with atopic eczema had higher initial urinary lactulose/rhamnose ratios than the controls. After dietary restriction, there was no overall change in permeability. Dietary therapy did however result in a large reduction in permeability in three of the nine children whose skin disease was improved, but a statistically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…Phenomena such as the increase of intestinal permeability and circulating immune complexes, can be associated with clinical symptoms in different organs and tissues, and this data are confirmed by the fact that increased intestinal permeability is reduced by effective elimination diet that excludes offending foods [15]. The higher incidence of food allergy in infants seems to be linked to the fact that infants are particularly prone to adverse reaction to cow’s milk proteins.…”
Section: Introductionmentioning
confidence: 98%
“…Phenomena such as the increase of intestinal permeability and circulating immune complexes, can be associated with clinical symptoms in different organs and tissues, and this data are confirmed by the fact that increased intestinal permeability is reduced by effective elimination diet that excludes offending foods [15]. The higher incidence of food allergy in infants seems to be linked to the fact that infants are particularly prone to adverse reaction to cow’s milk proteins.…”
Section: Introductionmentioning
confidence: 98%
“…52 53 Furthermore, increased intestinal permeability has been described in patients with food allergies, eczema and asthma compared with healthy subjects. [54][55][56][57] Finally, it has also been suggested that infants susceptible to the development of allergies are also susceptible to aberrant colonisation of the gut. However, this explanation seems less likely since we have controlled for familial history of atopy.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies that have examined relatively small numbers of patients found no evidence of altered permeability [84][85][86] while several others have found abnormalities in a subgroup of patients. [87][88][89] In at least some of these patients relief of symptoms has accompanied probiotic treatment 90 and in one study probiotics not only reduced the skin disease but also decreased elevated small intestinal permeability. 91 It is unclear from this study whether the increased permeability was a cause of the atopic dermatitis or an associated area of inflammation.…”
Section: Other Diseasesmentioning
confidence: 99%